Immune dysfunction following severe trauma: A systems failure from the central nervous system to mitochondria - Dobson, Geoffrey P.; Morris, Jodie L.; Letson, Hayley L. (Frontiers in Medicine, 2022)
When a traumatic injury exceeds the body’s internal tolerances, the innate immune and inflammatory systems are rapidly activated, and if not contained early, increase morbidity and mortality. Early deaths after hospital admission are mostly from central nervous system (CNS) trauma and circulatory collapse, and later deaths from hyperinflammation, immunosuppression, infection, sepsis, acute respiratory distress, and multiple organ failure. The molecular drivers of secondary injury include damage associated molecular patterns (DAMPs), pathogen associated molecular patterns (PAMPs) and other immune-modifying agents that activate the hypothalamic-pituitary-adrenal (HPA) axis and sympathetic stress response. Despite a number of drugs targeting specific anti-inflammatory and immune pathways showing promise in animal models, the majority have failed to translate. Reasons for failure include difficulty to replicate the heterogeneity of humans, poorly designed trials, inappropriate use of specific pathogen-free (SPF) animals, ignoring sex-specific differences, and the flawed practice of single-nodal targeting. Systems interconnectedness is a major overlooked factor. We argue that if the CNS is protected early after major trauma and control of cardiovascular function is maintained, the endothelial-glycocalyx will be protected, sufficient oxygen will be delivered, mitochondrial energetics will be maintained, inflammation will be resolved and immune dysfunction will be minimized. The current challenge is to develop new systems-based drugs that target the CNS coupling of whole-body function.